Níveis de proteína bruta na dieta para o híbrido : Pseudoplatystoma reticulatum x Leiarius marmoratus na fase inicial - Barbosa, Carolina Teixeira Costa Silva (2016)
The study aims to evaluate the requirement of crude protein (CP) in the diet of the Amazonian hybrid painted (female Pseudoplatystoma reticulatum x male Leiarius marmoratus) in the initial phase. The experimental period was 56 days, the animals were divided into 10 boxes of 250 liters, a total of 200 fish, 20 fish in each box. The experimental diets were formulated with five levels of crude protein (27, 30, 33, 36 and 39% CP). Every 15 days was performed biometrics of all fish. At the end of the trial period the fish were slaughtered to determine carcass yield, visceral fat and viscerossomatic and hepatossomatic indexes. Water features were favorable to animal performance during the trial period. The performance and carcass evaluations were evaluated and treatments 33, 36 and 39 crude protein in the diet worked best for this initial phase of the hybrid Pseudoplatystoma reticulatum x Leiarius marmoratus. But variables evaluated demonstrate that treatment with 33% of crude protein in the diet is suitable for the initial phase of Pintadinho Amazonian hybrid, providing greater final weight and smaller proportion of visceral fat. This value is lower than the level used for the fish in this initial phase, and thereby reduces the cost of production, encouraging investment in this crop.